A review of the contribution of livestock to food security, poverty alleviation and environmental sustainability in sub-Saharan Africa - Ehui, Simeon K. (1999)
Unlike developed countries, where people often eat too many animal products, most of the population of Sub-Saharan Africa eats too little of this type of food for good nutrition. The projected increase in demand for livestock in sub-Saharan Africa will have an important influence on food security and poverty alleviation. Livestock are vital to meeting agricultural productivity and sustainability objectives. As components of mixed crop-livestock farming systems, they play a critical role in the development of environmentally sound production systems. Where livestock have negative environmental impacts, this may be due to policy distortions and poor regulatory enforcement.